2019
DOI: 10.1111/trf.15456
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of transfusion‐transmitted cytomegalovirus infection using leukoreduced blood components in patients receiving seronegative umbilical cord blood transplantation

Abstract: BACKGROUND: Leukoreduced blood components have been widely implemented to prevent transfusiontransmitted cytomegalovirus (TT-CMV) in transplantation. Recent progress in leukoreduction technology has helped reduce the risk of TT-CMV in hematopoietic stem cell transplantation; however, its efficacy in umbilical cord blood transplantation (CBT) has not been systematically studied. STUDY DESIGN AND METHODS:We retrospectively analyzed the incidence of CMV infection in patients treated with CBT who received prestora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…In the United States, a 2017 survey reported 90% of responding institutions use leukoreduction as the primary TT-CMV prevention strategy; 40% of respondents indicated that seronegative blood use was by physician discretion in the absence of clinical guidelines. 27 Given the TT-CMV observations in our study and those in HSCT populations, [19][20][21][22][23] discontinuation of use of seronegative blood products for SOT recipients provides an evidence-based opportunity for transfusion cost reduction in settings where leukoreduced blood products are already being given. This may be further justified when the risk of TT-CMV is compared to the high incidence of donor-derived CMV and CMV reactivation when donors or recipients are seropositive; the latter risks are considered acceptable when managed using antiviral drugs and laboratory surveillance strategies.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In the United States, a 2017 survey reported 90% of responding institutions use leukoreduction as the primary TT-CMV prevention strategy; 40% of respondents indicated that seronegative blood use was by physician discretion in the absence of clinical guidelines. 27 Given the TT-CMV observations in our study and those in HSCT populations, [19][20][21][22][23] discontinuation of use of seronegative blood products for SOT recipients provides an evidence-based opportunity for transfusion cost reduction in settings where leukoreduced blood products are already being given. This may be further justified when the risk of TT-CMV is compared to the high incidence of donor-derived CMV and CMV reactivation when donors or recipients are seropositive; the latter risks are considered acceptable when managed using antiviral drugs and laboratory surveillance strategies.…”
Section: Discussionmentioning
confidence: 78%
“…In our previous 2002 study of SOT recipients receiving non-leukoreduced, unscreened blood products prior to universal leukoreduction we identified 3 cases of presumed TT-CMV infection, all symptomatic with fever or gastrointestinal identify any cases of TT-CMV infection among 182 recipients receiving 7903 leukoreduced and unscreened blood products. [19][20][21][22] Although Kekre et al 23 detected 1 case of TT-CMV infection when using leukoreduced blood alone, 3 cases were detected when using CMV leukoreduced and seronegative blood, suggesting that use of CMV seronegative blood in HSCT recipients when universal leukoreduction is already in place is unwarranted. Our study now demonstrates similar outcomes directly in the D−/R− SOT population, lending further support to the CMV SOT guidelines with respect to transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…В литературе описаны случаи заражения герпесвирусными инфекциями при переливании донорской крови и ее компонентов [8,9]. Современная эпидемиологическая обстановка по данной группе инфекций оценивается как напряженная.…”
unclassified
“…Для клеточно-ассоциированных патогенов, к которым относятся герпесвирусы, особенно актуальна лейкоредукция. Исследованиями показано, что после лейкоредукции с использованием лейкофильтров значимо снижается риск передачи ЦМВ [5,8,9], а ВЭБ после лейкофильтрации заведомо инфицированных доз концентрата тромбоцитов совсем не определяется [20]. Патогенредукция также относится к важным профилактическим мероприятиям, поскольку она эффективна в отношении большинства бактерий, простейших и вирусов, имеющих липидную оболочку [21][22][23].…”
unclassified